An app to maintain/improve the senior citizen's cognitive abilities - Tan, Cheryl Ying Xia (Nanyang Technological University, 2024)
As the global population ages, senior citizens often face challenges such as social isolation and a perceived lack of contribution to society. Cognitive decline further exacerbates these issues, reinforcing stereotypes and diminishing self-esteem. To address this, this project aims to develop a Unity-based game app tailored to enhance cognitive abilities in senior citizens. Focused on the concept of "magic numbers", the app guides users through exercises aimed at quick mental calculations, specifically calculating the square a of number. Our objective is to create an engaging and user-friendly interface that promotes cognitive stimulation while challenging societal perceptions about seniors' capabilities. Through this project, we seek to empower seniors to maintain their cognitive skills, foster positive self-image, and advocate for a more inclusive society.